2016
DOI: 10.1186/s12879-016-2130-x
|View full text |Cite
|
Sign up to set email alerts
|

Commercial sex and risk of HIV, syphilis, and herpes simplex virus-2 among men who have sex with men in six Chinese cities

Abstract: Background: Men who have sex with men (MSM) are at high risk of HIV and sexually transmitted infections (STIs) in China and globally. Engaging in commercial sex put them at even greater risk. This study estimated the prevalence of HIV/STIs among three subgroups of MSM: MSM who sold sex (MSM-selling), MSM who bought sex (MSM-buying), and non-commercial MSM (NC-MSM) and evaluated the relationship between commercial sex and HIV/STIs. Methods: We conducted a cross-sectional survey among MSM in six Chinese cities (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
4
16
1
1
Order By: Relevance
“…The per contact risk of HIV infection for condomless receptive anal sex is over three times that for condomless insertive anal sex (0.73% vs. 0.22%) [44]. In addition, the meta-analysis data indicate that nitrite inhalants users are more likely than nonusers to have CAI, thereby increasing their risk of HIV infection, similar to previously reported research [45]; however, in our meta-analysis, only three studies reported an association between condomless anal intercourse and an increased risk of HIV infection among MSM [15,26,30,46]. This surprising outcome may be due to the small sample sizes in these studies, resulting in insufficient statistical power to discern differences between condomless anal intercourse behaviors between nitrite inhalants users and nonusers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The per contact risk of HIV infection for condomless receptive anal sex is over three times that for condomless insertive anal sex (0.73% vs. 0.22%) [44]. In addition, the meta-analysis data indicate that nitrite inhalants users are more likely than nonusers to have CAI, thereby increasing their risk of HIV infection, similar to previously reported research [45]; however, in our meta-analysis, only three studies reported an association between condomless anal intercourse and an increased risk of HIV infection among MSM [15,26,30,46]. This surprising outcome may be due to the small sample sizes in these studies, resulting in insufficient statistical power to discern differences between condomless anal intercourse behaviors between nitrite inhalants users and nonusers.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, nitrite inhalants users may more likely to engage in commercial sexual behavior than nonusers in our meta-analysis. MSM who have ever sold sex to another male or bought sex from another male have higher levels of condomless anal intercourse and higher numbers of sexual partners in the past 6 months compared with those who have never been involved in commercial sex [46]. As these high-risk HIV-related factors associated with commercial sex are more common among MSM who engage in commercial sex, these MSM are therefore more likely to become infected with HIV, compared with MSM who do not participate in commercial sex.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of multiple drug use associated with syphilis infection corroborates the Antiretrovirals, Sexual Transmission Risk and Attitudes study findings,8 suggesting associations between increasing numbers of drugs used and increasing prevalence of sexual risk indicators, for example, condomless sex, group sex or sex party and having multiple new sex partners 19. MSM who had sex party experience were likely to have multiple sex partners, as expected 20. A study conducted in Europe showed that MSM who had group sex rarely over the past 6 months reported lower prevalence of syphilis infections than those who had frequent group sex,21 which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 87%
“…A study conducted in Europe showed that MSM who had group sex rarely over the past 6 months reported lower prevalence of syphilis infections than those who had frequent group sex,21 which is consistent with our findings. Having sex party experience expands high-risk sex partner networks, well known to increase syphilis risk 20. This study shows that MSM who had reported ever having a prior STI were four times more likely to be infected with syphilis.…”
Section: Discussionmentioning
confidence: 62%
“…In contrast, men having their first sex with a woman presents higher predicted probability of syphilis across all ages of sexual debut. Compared to MSM having first sex with a man, these subgroups were more likely to seek sex via non-Internet venues and have increased recent or lifetime female sex partners, which might include syphilis-at-risk female sex workers, increasing their exposure to contract syphilis through unprotected virginal sex [24, 45, 46]. …”
Section: Discussionmentioning
confidence: 99%